The Relationship Between Mother-Tongue Instruction and English Language Achievement Among Secondary School Students in Faskari Local Government Area of Katsina State, Nigeria - Nuraddeen Adamu Kanon-Haki; Karima Abdulkarim; Sule Muhammad (Universal Education Jurnal Teaching and Learning, 2026)
This study investigated the relationship between mother-tongue instruction and English language achievement among secondary school students in Faskari Local Government Area of Katsina State, Nigeria. Guided by Cummins’ Linguistic Interdependence Hypothesis, the study examined how the use of students’ first language influences comprehension, vocabulary development, and classroom participation during English language lessons. A correlational research design was adopted. The population comprised all secondary school students in Faskari LGA, from which a sample of 345 students was selected using stratified random sampling. Data were collected through a structured questionnaire validated by experts and tested for reliability, yielding a Cronbach’s alpha coefficient of 0.88. Descriptive statistics were used to summarize the data, while Pearson Product Moment Correlation was employed to test the hypotheses at a 0.05 level of significance. The findings revealed a strong and significant positive relationship between mother-tongue instruction and students’ comprehension, vocabulary development, and classroom participation. These results indicate that strategic use of the mother tongue enhances students’ understanding, promotes active classroom engagement, and supports English language learning. The study concludes that mother-tongue instruction, when systematically integrated with English teaching, serves as an effective pedagogical strategy for improving English language achievement among secondary school students. It is therefore recommended that educational policymakers and teachers encourage structured bilingual instructional practices to enhance learning outcomes in secondary schools.